2019
DOI: 10.1093/mnras/stz930
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic propagation model to the energy dependent rapid temporal behaviour of Cygnus X-1 as observed by AstroSat in the hard state

Abstract: We report the results from analysis of six observations of Cygnus X-1 by Large Area X-ray Proportional Counters (LAXPC) and Soft X-ray Telescope (SXT) on-board AstroSat, when the source was in the hard spectral state as revealed by the broad band spectra. The spectra obtained from all the observations can be described by a single temperature Comptonizing region with disk and reflection components. The event mode data from LAXPC provides unprecedented energy dependent fractional root mean square (rms) and time-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…For a QPO frequency of 1.56 Hz, the time lag between the δT in and δT e is about −1.5 ms, implying that the variation δT e occurs first. For Cygnus X-1, the time lag is similar for the same frequency, but is positive, implying that the variation δT in occurs first (Maqbool et al 2019). Thus, while for Cygnus X-1, the corona responds to a stochastic perturbation that occurs in the disk, for Swift J1658.2-4242 it is opposite, such that the QPO originates in the corona and the fluctuation propagates outwards towards the disk.…”
Section: Fitting the Energy Dependence Timing Propertiesmentioning
confidence: 94%
“…For a QPO frequency of 1.56 Hz, the time lag between the δT in and δT e is about −1.5 ms, implying that the variation δT e occurs first. For Cygnus X-1, the time lag is similar for the same frequency, but is positive, implying that the variation δT in occurs first (Maqbool et al 2019). Thus, while for Cygnus X-1, the corona responds to a stochastic perturbation that occurs in the disk, for Swift J1658.2-4242 it is opposite, such that the QPO originates in the corona and the fluctuation propagates outwards towards the disk.…”
Section: Fitting the Energy Dependence Timing Propertiesmentioning
confidence: 94%
“…Although Figure 3 (Top panel) gives an idea about temporal behavior of the system in frequency and energy realm, they neither provide an interpretation of physical behavior of the system nor its association to the time-averaged PDS. Hence to make such an association, we have modeled the observed fractional rms and timelag using the stochastic propagation model developed by Maqbool et al (2019). We present this result along with a comparison of the results of Cygnus X-1 in the following sections.…”
Section: Temporal Analysismentioning
confidence: 99%
“…Recent works carried out by Cowperthwaite & Reynolds (2014), Hogg & Reynolds (2016) and Ahmad et al (2018) have shown that for standard optically thick and geometrically thin disks the propagation time-scales are frequency dependent and are different from the viscous ones. Maqbool et al (2019) quantified this behavior for hot, optically thin, geometrically thick flows considering the propagation time from the transition region onwards. They also considered the Comptonized spectrum to arise from a single Comptonizing zone as opposed to multi Comptonizing zones assumed in previous works.…”
Section: Stochastic Propagation Modelmentioning
confidence: 99%
See 2 more Smart Citations